136k views
2 votes
Use the quadratic formula to find the solutions to the equation x^2-3x+1=0

2 Answers

3 votes

The answer is in the picture below! :)

|

V

Use the quadratic formula to find the solutions to the equation x^2-3x+1=0-example-1
User Cliffroot
by
4.9k points
5 votes

Answer:


x_(1)=(+3+√(5) )/(2)\\\\x_(2)=(+3-√(5) )/(2)

Explanation:

Using:


x=\frac{-b+-\sqrt{b^(2)-4*a*c} }{2*a}

we will have two solutions.

x^2-3x+1=0

So, a=1 b=-3 c=1


x_(1)=\frac{+3+\sqrt{-3^(2)-4*1*1} }{2*1}\\\\x_(2)=\frac{+3-\sqrt{-3^(2)-4*1*1} }{2*1}

We have two solutions:


x_(1)=(+3+√(5) )/(2)\\\\x_(2)=(+3-√(5) )/(2)

User Mike Ritacco
by
4.9k points